Utilization of Riasec Theory to Identify Career Personalities in Deaf Students: A Systematic Review - Pardi, Pardi (Al Makki Publisher, 2024)
A career is a process that a person experiences in his life. In the end, a person must have the skills to choose a career as a determinant of life in the future. Deaf people are people who lose the ability to hear, so they inhibit the processing of information through their hearing, whether or not they are wearing hearing aids. In general, deaf children have normal and average intelligence. Effective guidance needs to be based on accurate data. Therefore, before doing therapy, it is necessary to do an assessment first, which is to assess or recognize counselling in depth in various aspects. John Holland's theory helps identify students' career personalities according to types, traits and psychological characteristics (personality). It draws on the principles of Holland's theory, which groups individuals into six personality types and corresponding work environments. This study aims to provide practical guidance for parents, educators, and career counsellors. The aim is to improve the career readiness of deaf children and create a more inclusive and supportive environment for their professional growth.